The right infant nutrition: do nutrition and growth matter in the 6 to 24 month period? - Carlo Agostoni (Hygeia Press di Corridori Marinella, 2014)
In the last decades several studies tested the hypothesis that at early developmental stages certain foods or nutrients, in specific amounts, fed during limited sensitive periods, may lead to clinical alterations that take place decades later (early nutritional programming of long term health). In spite of suggestions from different early dietary habits, epidemiologic data show that episodes of rapid growth (growth acceleration hypothesis), whichever the dietary habits, are associated with later unfavorable health conditions and should be prevented. Early fast weight gain may be associated with increased likelihood of developing insulin resistance, dyslipidemic conditions, obesity, elevated blood pressure, and endothelial dysfunction. Accordingly, infant's growth pattern may represent the interaction between genetic background and environment, inclusive of nutrition. The branch of science focusing on these aspects is known as epigenetics. Different studies have shown on the other hand a reduced growth in infants with specific disorders (milk allergy, HIV) even before the overt clinical symptoms of the disease. Within this context the nutritionist's task is the prevention of deficiencies, but intervention strategies to prevent malnutrition should emphasize improvements in linear growth in the first 2-3 years of life rather than aim at gaining weight, to prevent the event of rapid early weight gain. The present constraints of the global economic crisis require cost/benefit analyses for all the interventions to optimize nutrition and growth in early years. Recent indications for complementary feeding indicate the beneficial effects of introducing earlier food items such as egg and fish, together with breastfeeding continuation through the first year, in reducing the later risk of immune allergic disorders and metabolic impairments.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou